Impact of Maternal Factors on Birth Parameters in Urban Affluent Pregnant Women - Borazjani, F.; Kulkarni, Shanuak S.; Ahmadi, K.A. (Pakistan Journal of Nutrition, 2011)
The objective of this study was to determine the effect of maternal nutritional factors on birth parameters among urban affluent pregnant women. A cross sectional study was carried out in Pune city of Maharashtra state among 156 singleton healthy pregnant women. Face to face interview method was undertaken of the pregnant women who were visiting for their monthly check up. During each interview, information was sought concerning the demography background of pregnant women and 24 h diet recall and also food frequency questionnaire. Each 1gr increase in maternal protein intake is associated with a 31.47gr increase in birth weight (95% CI, 5.36-57.59gr) and 0.158 cm increase in birth length (95% CI, 0.046-0.27 cm). Also there is positive contribution between percent of energy derived from protein and birth weight. In addition birth length predicted positively by % of energy derived from fat. In addition it exist the negative weakly association between energy intake with birth weight and also negative association between birth length and maternal carbohydrate intake. The study support that maternal dietary composition has an effect on fetal growth and pregnancy outcome.